Characterization of the outcome of CT angiography for pulmonary thromboembolism depending on age group and gender - Warley Ferreira Felix; Maria Auxiliadora Fortini Veloso; Marcos Eugênio Silva Abrantes; Ramon Vitor de Miranda (Brazilian Journal of Radiation Sciences)
Pulmonary thromboembolism is the third cause of morbimortality between acute cardiovascular diseases and for your diagnosis, Angiotomography is the most used exam in the current. When performing analyzes by gender and age group of the population participating in a study, that they submitted an angiotomography for pulmonary thromboembolism, it was observed that the female gender comprised 65.48% of the population studied with an average age group (55.86 ± 16,88) years and the male 34.52% with an age average of (56.86 ± 16.87) years. Thus, the contrast ratio by age groups between genders was studied, where statistical studies did not show significant differences.